Exploring different forms of technology-enhanced learning strategies in a handball coach education program - Murray, E.; Spencer, K.; Bennett, B. (International Sport Coaching Journal, 2023)
Effective and accessible coach education is a key part of sustainable sport development. Recent world events and inequitable resource division has led to an increase in the prevalence of remote learning. This study examines three methods of low-cost, simple technological-enhanced learning in handball coach education: Video On Demand, Interactive Video Learning, and Direct Remote Learning. Each intervention was examined under several relevant categories: accessibility, comprehensiveness, effectiveness, and empowerment, and compared against the others. All three methods were found to be applicable methods of remote coach learning with positive outcomes in learning and application. Video On Demand was very accessible and thought by participants to allow learning from varied sources. However, interactive methods (Interactive Video Learning and Direct Remote Learning) were preferred in most cases, as they promoted inter- and intrapersonal relational interactions and contextual informal as well as formal learning.